Menthone supplementation ameliorates systemic allergic inflammation in asthmatic mice via regulating Th2-skewed immune balance - Yi-Hsuan Su; Jin-Yuarn Lin (Elsevier, 2022)
Background: Menthone that is a monoterpene rich in Mentha × piperita L. has been found anti-inflammatory potential for treating various diseases. However, the effect of menthone supplementation in vivo on systemic allergic inflammation in allergic asthma has not been investigated yet.Purpose: To unravel the puzzle, menthone was administered by gavage to ovalbumin (OVA)-sensitized and challenged BALB/c mice for 5 weeks to evaluate the effects on allergic asthma.Study design: There were six groups in the experiment, including dietary control (DC group, 0 mg menthone/kg b.w./day), 8 (ML group), 40 (MM group) as well as 200 mg menthone/kg b.w./day (MH group), positive control (PC group, 3 mg dexamethasone/kg b.w. before OVA challenge) and non-treatment control (NTC group, normal mice without treatment).Methods: Changes in mediators of systemic immune responses including serum antibody titers, Th1/Th2 cytokines by splenocytes and pro-/anti-inflammatory cytokines by peritoneal macrophages of the experiment mice were analyzed using ELISA.Results: As a result, menthone supplementation significantly decreased Th2-polarized OVA-specific IgG1 and IgE titers, as well as total IgE levels. Menthone supplementation dose-dependently and significantly decreased IL-4 and IL-5 (Th2) secretions by splenocytes. Menthone supplementation decreased pro-/anti-inflammatory secretion ratios (TNF-α/IL-10) by peritoneal macrophages.Conclusion: Our results suggest that menthone supplementation may effectively ameliorate systemic allergic inflammation in the allergic asthmatic mice via regulating Th2-skewed immune balance.